Is the Wechsler Intelligence Scale for Children Third Edition UK (WISC-III UK Applicable to Ghana? - Edwin, A.K. (University of Ghana, 2001)
The study aimed at standardizing the Wechsler Intelligence Scale for Children Third Edition UK (WISC-III UK) for use with 200 Ghanaian children from selected schools between the ages of 6 years, to 11 years, 11 months. These children were also given the Raven's Coloured Progressive Matrices (RCPM). Subjects were in two groups. Private and public schools, distributed into 12 age groups. Comparisons were made based on the private public dichotomy and the 12 age groups. The study confirmed that individual's performance on the WISC-III is Influenced by his/her cultural milieu with children from the higher SES schools doing better on the test than those from the lower SES schools. The children from private schools were different from children from public schools on all the WISC-III UK subtests and the RCPM. There were also significant differences within the two School groups as well as some overlap between one of the private schools and one of the public schools. These findings support and add to the many in the literature, which indicate that differences exist in the performance of different cultural and socio-economic groups. The results also indicated that males and females did not differ Significantly from each other on almost all the subtests and RCPM except on the Mazes subtest. Although increasing age did not show a uniform improvement on scores, generally, children in the upper socio-economic groups did better than children in the lower classes. The performance of the WISC-III also correlated strongly with performance on the RCPM.
(Standardization of the WISC-III UK For Use in Accra Ghana)
MPhil. Psychology
Keywords: Raven's Coloured Progressive Matrices (RCPM); Wechsler Intelligence Scale for Children Third Edition UK (WISC-III UK); SES schools